IMPLEMENTASI FORECASTING PADA PERENCANAAN SISTEM PEMESANAN BUKU LKS (LEMBAR KERJA SISWA) MENGGUNAKAN ALGORITMA REGRESI LINEAR. (STUDI KASUS: TOKO BUKU DARUL ULUM, PUNGGUR, LAMPUNG TENGAH - Permata permata (Jurnal Data Mining dan Sistem Informasi, 2022)
Darul Ulum Bookstore is engaged in distributing LKS books to be sent to schools. The need for worksheets that support learning is one of the most important aspects of availability in the store. so it takes sufficient stock in the order at the beginning of the semester. In this case, the shop owner has difficulty in estimating the number of books to be ordered, so a calculation model is needed to estimate how many books will be ordered at the beginning of the semester. The Multiple Linear Regression method is one of the methods used to predict how many books will be ordered. This method uses the dependent variable and the independent variable as the basis by taking into account the initial stock of books for 2018 and 2019 as the independent variable (x) and the initial stock of 2020 as the dependent variable (y). The results of this study obtained a predictive accuracy value from each printing, namely for CV. Hasan Pratama with MAPE testing of 6.42% with very good indicators. CV. Pratama Mitra Aksara with MAPE testing of 23.52% the results of the indicators are feasible, and CV. Pilar Pustaka with MAPE testing of 6.75% the indicator results are very good. And visualization of predictive data using R-Markdown. Keywords: Linear Regression, Predicting, Interactive Website, R-Markdown